Exposure of bighorn sheep to domestic goats colonized with Mycoplasma ovipneumoniae induces sub-lethal pneumonia - Besser, Thomas E.; Cassirer, E. Frances; Potter, Kathleen A.; Foreyt, William J. (PloS one, 2017)
Bronchopneumonia is a population limiting disease of bighorn sheep (Ovis canadensis) that has been associated with contact with domestic Caprinae. The disease is polymicrobial but is initiated by Mycoplasma ovipneumoniae, which is commonly carried by both domestic sheep (O. aries) and goats (Capra aegagrus hircus). However, while previous bighorn sheep comingling studies with domestic sheep have resulted in nearly 100% pneumonia mortality, only sporadic occurrence of fatal pneumonia was reported from previous comingling studies with domestic goats. Here, we evaluated the ability of domestic goats of defined M. ovipneumoniae carriage status to induce pneumonia in comingled bighorn sheep. In experiment 1, three bighorn sheep naïve to M. ovipneumoniae developed non-fatal respiratory disease (coughing, nasal discharge) following comingling with three naturally M. ovipneumoniae-colonized domestic goats. Gross and histological lesions of pneumonia, limited to small areas on the ventral and lateral edges of the anterior and middle lung lobes, were observed at necropsies conducted at the end of the experiment. A control group of three bighorn sheep from the same source housed in isolation during experiment 1 remained free of observed respiratory disease. In experiment 2, three bighorn sheep remained free of observed respiratory disease while comingled with three M. ovipneumoniae-free domestic goats. In experiment 3, introduction of a domestic goat-origin strain of M. ovipneumoniae to the same comingled goats and bighorn sheep used in experiment 2 resulted in clinical signs of respiratory disease (coughing, nasal discharge) in both host species. At the end of experiment 3, gross and histological evidence of pneumonia similar to that observed in experiment 1 bighorn sheep was observed in both affected bighorn sheep and domestic goats. M. ovipneumoniae strains carried by domestic goats were transmitted to comingled bighorn sheep, triggering development of pneumonia. However, the severity of the disease was markedly milder than that seen in similar experiments with domestic sheep strains of the bacterium.